Sistemas de apoio à decisão clínica e o desfecho clínico na atenção primária: Uma revisão sistemática - Silva, Diego Francisco Januário (2019)
The aim of this study was to conduct a systematic review of the literature addressing the use of Clinical Decision Support Systems (CDSS) in Primary Health Care services, seeking to identify the relationships between the use of the Systems and the clinical outcomes. Characteristics of the systems in use are identified, as well as their practices and operations, and mapping the outcomes found when these resources are used. The research employed selected studies of Portuguese and English language, found in different medical databases. After refinement, debugging and systematization the references are presented in a detailed and comparative way demonstrating that CDSS are still in the development and refinement stage, their application still incipient (but with great potential) for the most diverse pathologies and clinical conditions. The results attributed to their use are quite confusing (and in many cases deficient), and clinical trials that trace the primary clinical outcomes are rarely carried out, leading to the accumulation of data only on secondary or compound outcomes, making it difficult to evaluate the systems. The results indicate a relative efficiency in the use of CDSS for diagnosis and prevention situations, with limited efficiency in the treatment phase. Finally, there is insufficient data to establish whether CDSS generates more favorable or unfavorable primary clinical outcomes in Primary Health Care.